Impact of Islamic Philanthropy on Educational Development: A Case Study of BAZNAS in Daerah Istimewa Yogyakarta - Nailis Sa’adah; Layyin Natus Shofiyah; Khalid Husein Abdurrahman; Aning Puspita Ningrum; Alaina Nafila Zahfana (Journal of Islamic Education Management Research, 2023)
Purpose – This study aims to explore the evolution and current state of Islamic philanthropy in Indonesia, focusing specifically on its impact on educational development in the region of Daerah Istimewa Yogyakarta (DIY). Design/methods– A qualitative research design was employed in this field study, conducted at BAZNAS DIY. Data collection involved interviews, observations, and document analysis to gather comprehensive and in-depth information. Findings – The research reveals that Islamic philanthropy, deeply ingrained in cultural and religious doctrines, significantly contributes to addressing socio-economic challenges in education. Philanthropic activities managed by BAZNAS DIY, such as zakat, sedekah, infak, wakaf, and others, have played a crucial role in fostering educational opportunities and enhancing welfare. Programs like DIY Cerdas, DIY Taqwa, DIY Sehat, DIY Sejahtera, and DIY Peduli have been successful in improving educational infrastructure, supporting needy students, and addressing broader societal needs. Research implications/limitations – The study acknowledges limitations in its scope and generalizability. It concludes with recommendations for future research to further analyze the impact of Islamic philanthropy on a broader scale and across different sectors, to gain a more comprehensive understanding of its influence. Practical implications – The findings of this study provide valuable insights for educational institutions and policymakers. They underscore the importance of effective infrastructure management and human resource development in optimizing the benefits of philanthropic initiatives in the field of education. Originality/value –This study contributes original insights into the role of Islamic philanthropy in the educational development of Daerah Istimewa Yogyakarta, highlighting how religious and cultural practices can be harnessed to address educational and socio-economic challenges in the region.